Positive Emotions and Addiction - Katerina , Flora (International Journal of Psychosocial Rehabilitation, 2015)
Despite the clinical observations that indicate a possible connection between emotions, addictive behavior and treatment, there is not sufficient research on the role of positive emotions in addiction and addiction treatment. The present study aims at the examination of the role of positive emotions in the process of therapy, especially viewing it as an important factor influencing outcome. The sample consisted of 157 clients undergoing substance abuse therapy in a residential treatment program. The results indicate the significance of positive emotions and the differentiations of impact in various treatment stages. Taking into account the role of emotions in the development of addictive behavior, this study demonstrates the complex role of this factor in the addiction field, with various implications for research and clinical practice.